The Effects of Earnigs Volatility, Net Income and Comprehensive Income on Stock Prices on Banking Companies on the Indonesia Stock Exchange - Rusdiyanto, Rusdiyanto; Narsa, I. Made (International Review of Management and Marketing, 2019)
This paper aims to analyze the effect of earnings volatilty, net income and comprehensive income on stock prices on banking companies on the Indonesia Stock Exchange in the period of 2011 to 2016. This paper uses a quantitative approach by using secondary data consisting of 174 data of commercial banks on the Indonesia Stock Exchange, from 2011 to 2016 obtained from the Indonesia Stock Exchange website www.idx.co.id. and www.yahoofinance.com, The analysis technique used in this study is multiple linear regression. hese results indicate that net income has a positive and significant effect on the level 5% statistic of stock prices, and could be used by investors in conducting fundamental analysis to have relevant information. While earnings volatility and comprehensive income do not have an influence on stock prices, meaning that even though high earnings volatility and comprehensive income tend to have no value relevance to stock prices. Previous research has done a lot to tests of earning volatility, net income on stock prices, the results conclude that earnings volatility, net income affect stock prices. So the novelty in this study is to include a comprehensive income variable, because the Statement of Financial Accounting Standards No.1 changes the terminology of the income statement into a statement of comprehensive income. Keywords: Share price, Earnings Volatility, Net Income, Comprehensive Income JEL Classifications: D23, L2 DOI: https://doi.org/10.32479/irmm.8640